Research Support in Australian Academic Libraries: Services, Resources, and Relationships - Haddow, Gaby; Mamtora, J. (Routledge, 2017)
In the last decade Australian academic libraries have increasingly aligned their research support services with assessment criteria used in the national research evaluation exercise (Excellence for Research in Australia). The same period has seen growing interest in research impact outside of traditional measures, such as bibliometrics. Social media has provided opportunities for research dissemination and new tools, altmetrics, to measure these activities have emerged. This article reports on research into the extent and nature of research support services at Australian academic libraries, how the services are managed, and the factors that influence their development and delivery. Quantitative and qualitative research methods were used to compare the findings with an earlier study and to provide a deeper understanding of research support in Australia. Three key themes, services, staff and resourcing, and relationships, are discussed in relation to the management and challenges faced in providing research support.